Age and moral disgust: An experimental priming effects vignette study - Guido Corradi; Pilar Aguilar; Fernando Aguiar; Antonio Olivera-La Rosa (PLoS ONE, 2025)
Disgust influences how people perceive and judge moral violations. Individuals who are more sensitive to disgust often judge such violations more harshly. This sensitivity may change depending on the context, like the age of the person committing the act. However, there’s limited and inconsistent evidence on how disgust sensitivity and feelings of disgust affect moral judgments toward older adults. This study aimed to find out if disgust sensitivity and induced feelings of disgust affect moral judgments differently based on the age of the person involved. Specifically, we examined whether people relate their disgust sensitivity differently when judging actions by young versus old individuals and whether showing disgusting images influences the harshness of moral judgments differently depending on the actor’s age. We conducted a preregistered experiment with 235 adult participants. Participants were randomly assigned to one of two groups: “Old” or “Young.” They read 24 stories about moral violations committed by either old or young individuals. Before each story, participants were briefly shown an image that was either disgusting, sad, or neutral. They then rated the acceptability of the behavior on a scale. Participants also filled out questionnaires measuring their disgust sensitivity, attitudes toward age, and emotions toward young and old people. The findings showed that higher disgust sensitivity was linked to harsher moral judgments, regardless of the age of the person committing the violation. This means that how sensitive someone is to disgust affects their moral judgments in the same way for both young and old actors. However, when participants were shown disgusting images before reading about an older person committing a moral violation, they judged the behavior less harshly compared to when the actor was young. This effect was not seen with sad or neutral images. There was also no significant interaction between the type of image shown and the participant’s disgust sensitivity. The study suggests that disgust has a complex role in moral judgments. While personal sensitivity to disgust leads to harsher judgments no matter who is involved, feelings of disgust induced by images can influence judgments differently based on the age of the person committing the act.